HUKUM TALAK TIGA SEKALIGUS PADA KOMUNITAS SALAFI (STUDI KASUS KECAMATAN NIBUNG HANGUS KABUPATEN BATU BARA) - Azwani Lubis; Hasbullah Ja'far; Suriana (Wahdatul Ulum Institute, 2023)
The Islamic religion regulates human relationships with Allah, human relationships with humans, human relationships with objects and the natural surroundings. One thing that is regulated in human relations with humans is the issue of marriage. The marriage which was hoped to form an eternal family, sakinah, mawaddah, warahmah apparently had to fail in the middle of the road. Household conditions that experience quarrels, disagreements, so that they cannot be reconciled, Islam provides a solution of divorce or divorce. According to the Four Schools, divorce itself has the numbers one, two and three, as is the opinion of the Salafi community in Nibung Hangus District, Batu Bara Regency. However, the case is different in calculating three talaqs at once, the Four Schools agree that the imposition of three talaqs at once is counted as triple talaq, while the Salafi Community is of the opinion that three talaqs at once are counted as one talaq. Therefore, this thesis is entitled about the Law of Triple Talaq at Once in the Salafi Community (Case Study of Nibung Hangus District, Batu Bara Regency. The most important thing in this thesis is that triple talaq at once in the Salafi Community is counted as one talaq. The Salafi Community gives the reason that in this era Prophet Muhammad SAW was a friend of Rukanah, he divorced his wife with three divorces at once. However, he regretted it and then he met Rasulullah SAW and said